Decision Support System for Appointment Assignment of Honorary Using TOPSIS Method - Hariati Husain; Citra Yustitya Gobel; Santawali Santawali (The IJICS (International Journal of Informatics and Computer Science), 2021)
The Honorary Staff Appointment and Assignment Program initiated by the Education Office of North Gorontalo Regency is one of the regional responses to overcome the shortage of teachers in remote areas and islands [1]. The purpose of this study is to build a decision support systemv that is used to assist the Education Office of North Gorontalo Regency in the process of appointing and assigning honorary staff. This study uses the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. This method is based on the concept that the best chosen alternative not only has the shortest distance from the positive ideal solution, but also has the longest distance from the negative ideal solution. This method is widely used to complete practical decision making [2]. The results of this study are by using the TOPSIS method in a decision support system that can facilitate decision makers related to the issue of the Handling and Assignment of Honorary Personnel at the Education Office of North Gorontalo Regency, especially in the assessment process according to predetermined criteria. The results of this assessment took a sample of 3 honorary candidates with the best score alterative obtained by a total value of 0.74 with the results being accepted as honorary